(untitled) (Minerva. Revista de Filología Clásica, 2019)
Mithraism is one of the most mysterious religions in the World. In fact, it was a mystery, a cult where initiates were supposed to remain silent about it to the profanes. These cults also offered the promise of eternal salvation to them. Little is known about Mithras and its cult, and so it remains more than a mystery. We could say almost the same about Arthuriana and some of its most important characters: they are a mystery in History, Folklore and Literature. However, British author Bernard Cornwell has mixed up both mysteries into one in his thrilling and mind-boggling trilogy The Warlord Chronicles, published between 1996 and 1998. This kaleidoscopic trilogy retells Arthur’s deeds and miseries from the moment his nephew Mordred is born until his final departure to Camlann, through the eyes of his best friend, Derfel Cadarn, a Mithraist. Derfel shows how Christianity triumphs over the rest of the pagan religions, most of the times with no fair play. We will see in this article how some of the actions in the trilogy symbolise the death of Paganism, the mystery of Mithras included, and the final triumph of Christianity.